2023
DOI: 10.1073/pnas.2300085120
|View full text |Cite
|
Sign up to set email alerts
|

Generating dual-active species by triple-atom sites through peroxymonosulfate activation for treating micropollutants in complex water

Abstract: The peroxymonosulfate (PMS)-triggered radical and nonradical active species can synergistically guarantee selectively removing micropollutants in complex wastewater; however, realizing this on heterogeneous metal-based catalysts with single active sites remains challenging due to insufficient electron cycle. Herein, we design asymmetric Co–O–Bi triple-atom sites in Co-doped Bi 2 O 2 CO 3 to facilitate PMS oxidation and reduction simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 172 publications
(47 citation statements)
references
References 55 publications
(73 reference statements)
0
36
0
Order By: Relevance
“…TPPO is refractory to biological degradation, but ultrasonic irradiation and the addition of radical promoters can promote its degradation in water. 89,90 The degradation products are typically more toxic than TPPO. 89 Previous studies have shown that reactions with OH radicals are the main atmospheric and aquatic loss processes of OPEs.…”
Section: Source Characteristicsmentioning
confidence: 99%
“…TPPO is refractory to biological degradation, but ultrasonic irradiation and the addition of radical promoters can promote its degradation in water. 89,90 The degradation products are typically more toxic than TPPO. 89 Previous studies have shown that reactions with OH radicals are the main atmospheric and aquatic loss processes of OPEs.…”
Section: Source Characteristicsmentioning
confidence: 99%
“…Therefore, the composite material increases the activation site, and some sites also have the adsorption capacity of OCs. This can shorten the ROS migration distance and improve the degradation rate. ,, Bimetallic catalysts can also adjust the valence state of Co and maintain continuous activity of the catalyst. In this context, we will mainly introduce the improvement of bimetallic composites mainly composed of Fe, Cu, Mn, and Ce compounds on the performance activated PMS by Co-based catalysts.…”
Section: Theoretical Calculation Of Pms-aops Involving Cobalt-based H...mentioning
confidence: 99%
“…The global average surface temperature is increasing with continually increasing greenhouse gas emissions and will increase by nearly 4 °C by 2100 according to the Intergovernmental Panel on Climate Change (IPCC) . In addition, extreme climate events such as heat waves will increase dramatically and last longer in the future. , Thus, ocean warming (OW) has become a global threat to ocean ecosystems, which could influence the physiological variability of phytoplankton and thereby impact the primary production and carbon cycle of ocean ecosystems. In addition, global warming can alter the environmental risk of anthropogenic contaminants, and, conversely, anthropogenic contaminants have the potential to increase the susceptibility of organisms to OW. As emerging contaminants, plastics caused the global ocean problem that is attracting much attention. Plastic pollution from anthropogenic activities in the ocean is increasing . More than 10 million tons of plastic debris were reported to be released into the marine environment each year. ,, The environmental concentration of microplastics (MPs, plastic debris <5 mm) can reach ∼>1000 particles/L in open and coastal water and 76,000 particles/L in polluted coastal regions .…”
Section: Introductionmentioning
confidence: 99%